623 MINIMALLY INVASIVE VERSUS OPEN MCKEOWN FOR PATIENTS WITH ESOPHAGEAL CANCER: A RETROSPECTIVE STUDY. (17th September 2021) - Zheng, Yan; Xing, Wenqun; Liu, Xianben; Sun, Haibo
Abstract:  : McKeown Minimally invasive esophagectomy(McKeown-MIE) offers advantages in short-term outcomes compared with McKeown open esophagectomy(McKeown-OE). However, debate as to whether MIE is equivalent or better than OE regarding survival outcomes is ongoing. The aim of this study was to compare long-term survival between McKeown-MIE and McKeown-OE in a large cohort of esophageal cancer(EC) patients. Methods: We used a prospective database of the Thoracic Surgery Department at our Cancer Hospital and included patients who underwent McKeown-MIE and McKeown-OE for EC during January 1, 2015, to January 6, 2018. The perioperative data and overall survival(OS) rate in the two groups were retrospectively compared. Results: We included 502 patients who underwent McKeown-MIE (n = 306) or McKeown-OE (n = 196) for EC. The median age was 63 years. All baseline characteristics were well-balanced between two groups. There was a significantly shorter mean operative time (269.76 min vs. 321.14 min, P < 0.001) in OE group. The 30-day and in hospital mortality were 0 and no difference for 90-day mortality (P = 0.116). The postoperative stay was shorter in MIE group, 14 days and 18 days in the MIE and OE groups(P < 0.001). The OS at 32 months was 76.82% and 64.31% in the MIE and OE groups (P = 0.001); hazard ratio(HR) (95% CI): 2.333 (1.384–3.913). Conclusion: These results showed the McKeown-MIE group was associated with a better long-term survival, compared with open-MIE for patients with resectable EC.